In vivo CRISPR screening identifies POU3F3 as a novel regulator of ferroptosis resistance in hepatocellular carcinoma via retinoic acid signaling - Yu Tian; Xin Bao; Shan Lei; Youcai Huang; Xiaoling Wang; Yanyang Tu; Qinglian He; Feixiang Zhang; Haicheng Xu; Milad Ashrafizadeh; Gautam Sethi; Furong Wang; et al. (Cell Communication and Signaling)
Abstract Background Sorafenib, a ferroptosis agonist, is a first-line treatment for advanced hepatocellular carcinoma (HCC). However, its clinical efficacy is limited due to drug resistance, resulting in modest improvements in patient survival. Hence, the present study has been designed to identify critical molecular targets associated with sorafenib resistance and investigate the potential inhibitors in overcoming this therapeutic challenge. Methods In vivo whole-genome CRISPR/Cas9 library screens were conducted to identify resistance factors to ferroptosis agonists, such as RSL3 and sorafenib, in HCC. The effects and underlying molecular mechanisms of these resistance factors were investigated in HCC cells using ferroptosis detection assays, xenograft tumor models, chromatin immunoprecipitation (ChIP), and dual-luciferase reporter assays. Potential inhibitors targeting these factors were evaluated through computer-aided virtual screening, molecular dynamics simulations, surface plasmon resonance analysis, and functional evaluations. Results A retinoic acid metabolism gene cluster, including ADH4, ALDH1A1, ALDH1A3, FABP5, RBP1, and RDH10, was found demonstrating upregulation in HCC cells treated with ferroptosis agonist, sorafenib. This gene cluster contributes to the ferroptosis resistance by producing the strong reducing agent retinoic acid. The transcription factor POU3F3 was identified as a key regulator for the retinoic acid metabolism gene cluster, which simultaneously binds to their promoters, increasing their transcription and promoting retinoic acid production. Knockdown of POU3F3 significantly enhanced the pro-ferroptotic and inhibitory effects of sorafenib on HCC cells by suppressing retinoic acid metabolism. Furthermore, rosarin was identified as a POU3F3 inhibitor, with an equilibrium dissociation constant of 7.57 µM, and demonstrated a synergistic effect with sorafenib against HCC cells both in vitro and in vivo. Conclusions According to the results, POU3F3 acts as a protective regulator against sorafenib-induced ferroptosis in HCC cells by enhancing the transcription of multiple retinoic acid metabolism genes and promoting retinoic acid production. The POU3F3 inhibitor, rosarin, shows potential as an ideal candidate for overcoming sorafenib resistance in HCC.